Sustainability in rural activity: A study in a small property in northwest gaúcho (Research, Society and Development, 2022)
Sustainability is a topic that has been growing in discussions and has been addressed with great intensity in studies on the subject. Given its importance, the objective of the study is to use a specific sustainability model for small rural organizations such as the case of MASPPR, the topic is the subject of proposals for discussion in the area of agriculture. This work analyzed how sustainability indicators can help rural producers to promote improvements in management and performance processes in order to make them more sustainable, based on the MASPPR model. The research was classified as descriptive, case study, documentary and qualitative. To carry out this research, data collected from documents, observation and semi-structured interviews were used to complement the data obtained, based on a construct supported by the MASPPR model. The findings indicate the sustainability of the property, around 72.08%. Such representativeness is possible, since all the dimensions analyzed (economic, social and environmental), when observed individually, were greater than 50%, with an emphasis on the environmental dimension, in which sustainability was 100%. With this, it is understood that knowing to what extent the sustainability indicators of each dimension are present in the economic activities of the investigated rural property can help in the improvement of production processes, as well as in the decision making regarding to improve its economic controls. and financial and their socio-environmental indicators.